Acquired resistance to temsirolimus is associated with integrin α7 driven chemotactic activity of renal cell carcinoma in vitro - Engl, Tobias (Oncotarget, 2018)
The mechanistic target of the rapamycin (mTOR) inhibitor, temsirolimus, has significantly improved the outcome of patients with renal cell carcinoma (RCC). However, development of temsirolimus-resistance limits its effect and metastatic progression subsequently recurs. Since integrin α7 (ITGA7) is speculated to promote metastasis, this investigation was designed to investigate whether temsirolimus-resistance is associated with altered ITGA7 expression in RCC cell lines and modified tumor cell adhesion and invasion. Caki-1, KTCTL-26, and A498 RCC cell lines were driven to temsirolimus-resistance by exposing them to temsirolimus over a period of 12 months. Subsequently, adhesion to human umbilical vein endothelial cells, to immobilized fibronectin, or collagen was investigated. Chemotaxis was evaluated with a modified Boyden chamber assay and ITGA7 expression by flow cytometry and western blotting. Chemotaxis significantly decreased in temsirolimus-sensitive cell lines upon exposure to low-dosed temsirolimus, but increased in temsirolimus-resistant tumor cells upon reexposure to the same temsirolimus dose. The increase in chemotaxis was accompanied by elevated ITGA7 at the cell surface membrane with simultaneous reduction of intracellular ITGA7. ITGA7 knock-down significantly diminished motility of temsirolimous-sensitive cells but elevated chemotactic activity of temsirolimus-resistant Caki-1 and KTCTL-26 cells. Therefore, ITGA7 appears closely linked to adhesion and migration regulation in RCC cells. It is postulated that temsirolimus-resistance is associated with translocation of ITGA7 from inside the cell to the outer surface. This switch forces RCC migration forward. Whether ITGA7 can serve as an important target in combatting RCC requires further investigation.